TANGGUNG JAWAB PENYIDIK DALAM MENGAMANKAN BARANG BUKTI TINDAK PIDANA NARKOTIKA DI WILAYAH HUKUM KEPOLISIAN DAERAH RIAU - RA, M. FAUZY; Effendi, Erdianto; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In 2018 the handling of drug crime cases in Riau has increased, comparedto 2017, the number of drug case handling rose from 1395 to 1900 cases. Thenumber of suspects also increased, from 1949 suspects in 2017 to 2647 suspectsin 2018. In the data, the number of evidence of drug addiction increased but itwas found that in the investigation process the amount of evidence secured wasreduced in number. The cause of the many cases in securing evidence of narcoticscrimes committed by investigators occurring in Indonesia cannot be deniedbecause of the lack of professionalism and performance of law enforcementofficers. If after the process takes place there is an error in determining thesuspect, then it can be questioned to the extent that officers and investigators playa role with their responsibilities in carrying out criminal proceedings.This type of research can be classified in the type of sociological legalresearch (empirical), because in this study the author immediately conductsresearch on the location or place under study in order to provide a complete andclear picture of the problem under study. This research was carried out in theRiau Regional Police jurisdiction, while the population and samples were theRiau Regional Police, Investigators of the Riau Regional Police and Actors ofNarcotics. The data sources used are primary data, and secondary data. Datacollection techniques in this study were interviews, questionnaires, and literaturereview.The conclusions that can be obtained from the results of the study areFirst, Legal Arrangements concerning investigations in securing evidence ofNarcotics crime are clearly and clearly regulated, but in practice are still oftenignored by law enforcement officials in conducting investigations. Second, theinvestigator's responsibility in securing evidence of narcotics crime, especially inthe Riau Regional Police jurisdiction, is still unprofessional in securing evidenceof narcotics crime and Third, Riau Regional Police Factors and Constraints insecuring evidence of Narcotics crime include lack of integrity of investigators whoare authorized to secure evidence of Narcotics crimeKeywords: Responsibility, Investigator, Evidence, Crime, Narcotics,